Performance of new clones of Hevea. III. Potential selections for the plateau region of Votuporanga, São Paulo State, Brazil - Gonçalves, Paulo de Souza; Bortoletto, Nelson; Ortolani, Altino Aldo; Belletti, Giselle Olmos; dos Santos, Wagner Rodrigues (Pesquisa Agropecuaria Brasileira, 1999)
The present paper shows the results of the first selection of 25 rubber tree clones (Hevea brasiliensis (Willd. ex Adr. de Juss.) Müell. Arg.). Most of them are introductions, originated in selections obtained from different places. After multiplied, the clone evaluation was conducted in a small scale trial under a randomized complete block design established at Votuporanga Experimental Station in São Paulo State, Brazil. The evaluated characters were yield, vigour expressed by stem girth, bark thickness and number of latex vessel rings. The clones IAN 3156, IAC 40, 7/6, 3/5 e 3/1 were classified as high yielding in the first year of tapping. They produced 124%, 105%, 27%, 26% and 19% higher compared with the RRIM 600. The secondary characteristics, such as stem girth, bark thickness, and number of latex vessel rings of the tested clones are discussed. A complementary evaluation in large scale trials is suggested, aiming to evaluate besides yielding other secondary characters with purpose of future recommendation of planting materials to the industry.